Homologous and heterologous expression of grapevine E-(β)-caryophyllene synthase (VvGwECar2). (November 2016) - Salvagnin, Umberto; Carlin, Silvia; Angeli, Sergio; Vrhovsek, Urska; Anfora, Gianfranco; Malnoy, Mickael; Martens, Stefan
Abstract: E- ( β )-caryophyllene is a sesquiterpene volatile emitted by plants and involved in many ecological interactions within and among trophic levels and it has a kairomonal activity for many insect species. In grapevine it is a key compound for host-plant recognition by the European grapevine moth, Lobesia botrana, together with other two sesquiterpenes. In grapevine E- ( β )-caryophyllene synthase is coded by the VvGwECar2 gene, although complete characterization of the corresponding protein has not yet been achieved. Here we performed the characterization of the enzyme after heterologous expression in E. coli, which resulted to produce in vitro also minor amounts of the isomer α-humulene and of germacrene D. The pH optimum was estimated to be 7.8, and the Km and Kcat values for farnesyl pyrophosphate were 31.4 μM and 0.19 s −1 respectively. Then, we overexpressed the gene in the cytoplasm of two plant species, Arabidopsis thaliana and the native host Vitis vinifera . In Arabidopsis the enzyme changed the plant head space release, showing a higher selectivity for E- ( β )-caryophyllene, but also the production of thujopsene instead of germacrene D. Overall plants increased the E- ( β )-caryophyllene emission in the headspace collection by 8-fold compared to Col-0 control plants. In grapevine VvGwECar2 overexpression resulted in higher E- ( β )-caryophyllene emissions, although there was no clear correlation between gene activity and sesquiterpene quantity, suggesting a key role by the plant regulation machinery. Graphical abstract: We studied a grapevine E- ( β )-caryophyllene synthase, performing first a characterization of the enzyme, and then creating plants which overexpress it and analysing their volatile emission by headspace collection. Highlights: E- ( β )-caryophyllene synthase was expressed in three different systems. There are differences in products formation and selectivity among the systems. Possibility to use these plants to study the role of E- ( β )-caryophyllene as a semiochemical.